2019
DOI: 10.1097/md.0000000000018036
|View full text |Cite
|
Sign up to set email alerts
|

CUL4A expression is associated with tumor stage and prognosis in nasopharyngeal carcinoma

Abstract: Cullin 4A (CUL4A) is a protein of E3 ubiquitin ligase with many cellular processes. CUL4A could regulate cell cycle, development, apoptosis, and genome instability. This study aimed to analyze the expression of CUL4A in nasopharyngeal carcinoma (NPC) tissues and the associations of CUL4A expression with prognostic significance. A total of 115 NPC patients were collected to assess the protein expression of CUL4A by immunohistochemistry, so as to analyze the relationships between CUL4A expression and clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…CUL4A has similar oncogenic effects in nasopharyngeal carcinoma. The expression of CUL4A has been directly related to cancer stage and prognosis in nasopharyngeal carcinoma [26]. Meanwhile, we found that an increased transcriptional level of CUL4A was shown in HNSCC samples, and the level of CUL4A mRNA could be correlated to clinic-pathological features.…”
Section: Discussionmentioning
confidence: 76%
“…CUL4A has similar oncogenic effects in nasopharyngeal carcinoma. The expression of CUL4A has been directly related to cancer stage and prognosis in nasopharyngeal carcinoma [26]. Meanwhile, we found that an increased transcriptional level of CUL4A was shown in HNSCC samples, and the level of CUL4A mRNA could be correlated to clinic-pathological features.…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, overexpression of CUL4A reduced cisplatin efficacy in HNSCC models. Since CUL4A has been previously reported to be overexpressed in nasopharyngeal and esophageal squamous cell carcinoma, this provides further rationale for the investigation of pevonedistat for HNSCC therapy [ 42 , 43 ]. Surprisingly, the augmentation of cisplatin-induced DNA damage and apoptosis by pevonedistat or CUL4A knockdown was shown to be mediated through the downregulation of DDB2, which is required for NER.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies found that CUL4A overexpression also occurred in the prostate, colon, liver, as well as lung cancer [ 12–15 ]. Of note, it was evidenced that CUL4A was overexpressed in NPC [ 16 ], nonetheless, the role of CUL4A, as well as its mechanism, has not been revealed.…”
Section: Introductionmentioning
confidence: 99%